GERAKAN DAKWAH ANREGURUTTA H. MUHAMMAD ARSYAD LANNU DI KABUPATEN SOPPENG - Roslan Roslan; Muliaty Amin; Andi Aderus (Jurnal Dakwah Tabligh, 2020)
The main problem in this study is the Anregurutta  H. Muhammad Arsyad Lannu Da'wah Movement (the year 1950-2011 AD) in Soppeng Regency, from the subject matter, was broken down into several sub-problems namely, 1) How is the Biography of Anregurutta H. Muhammad Arsyad Lannu. 2) How the Anregurutta Da'wah Movement H. Muhammad Arsyad Lannu. The results showed that Anregurutta named H Muhammad Arsyad Lannu, was born in Tenggapadange, December 31, 1930, male, Muslim lived in Maccini Rompegading Village and he had a wife named Hj. Yamma was born in Kacimpang on 31 December 1932 and thank God he was blessed with 7 children. The first child Ridwan, the second H. Syukri, the third Subu, the fourth H Emperor, the fifth Wittri, the sixth Muh Huzari, to Muh Ahyar, his father's name was Lannu, the name of Bungaa's mother. Both religious life (Islam) at that time was still very much influenced by the belief in animism. Pattojo society in the majority religion of Islam but there are indeed people who still know things mystical or still believe in the occult. The preaching movement carried out by Anregurutta H. Muhammad Arsyad Lannu covers the education of the boarding school coach, extracurricular. Anregurutta H. Muhammad Arsyad Lannu in his formation he fostered the community and students and students in terms of morals, ethics, morals. In addition to the style of the movement also found forms of propaganda movements namely preaching bi al Lisan (speaking), bi al hal (actions / exemplary), bi al qalaam (writing), also found movement strategies and efforts to succeed the movement.